A Profile of the Critical Thinking Skills of Prospective Elementary School Teachers Regarding the Concept of the Human Digestive System - Mega Laeni; Frida Yassar Maula (Journal of World Science, 2026)
Critical thinking skills are essential competencies that students who are prospective elementary school teachers must possess to face the challenges of the 21st century. This research aims to analyze the critical thinking ability profile of prospective elementary school teacher students on the concept of the human digestive system. The research method used was quantitative descriptive with 48 research subjects of the second semester of the PGSD Study Program. The data collection instrument was in the form of an essay test of 10 questions that included five indicators of critical thinking. The results showed that the average score of students' critical thinking ability was 23.19 (57.97%) which was included in the medium category. Based on the achievement of indicators, the highest percentage was achieved in the concluding indicator (66%), while the lowest percentage was found in the indicator of building basic skills (51%). This shows that although students are able to draw contextual conclusions, they are still weak in formulating in-depth scientific arguments.